The Third Sex - Willy, 1859-1931 (Book collections on Project MUSE., 2007)
"This first-ever English edition of The Third Sex provides a goldmine of information about hidden gay culture and an unrivaled personal record of European mores between world wars. In describing some of the most conspicuous homosexual personalities of the era, including the champion for tolerance Dr. Magnus Hirschfield and the transvestite American trapeze artist Barbettee, Willy is notoriously free from prudery. An introduction and copious notes by translator Lawrence R. Schehr supply important background on these colorful personalities throughout the text. In guiding readers through Willy's breezy and witty narrative, Schehr unpacks the fascinating and delightful puns buried in this first-hand account of gay men's culture."--Jacket.